The post-fossil subsidy age of the United Arab Emirates. Issue 5 (December 2015) - Poon, Chun Yu Jonathan
Abstract : With subsidies for oil and gas coming to an end in the United Arab Emirates, Chun Yu Jonathan Poon assesses the likely impact for renewable energy development in the country and around the world.